The big finish [large type - Fossey, Brooke (Thorndike Press large print basic, 2020)
"For Duffy Sinclair life boils down to one simple thing: maintaining his residence at the idyllic Centennial Assisted Living. Without it, he's destined for the roach-infested nursing home down the road--and after wasting the first eighty-eight years of his life, he refuses to waste away for the rest. So, he keeps his shenanigans to the bare minimum with the help of his best friend and roommate, Carl Upton. Then Carl's granddaughter Josie climbs through their bedroom window with booze on her breath and a black eye. Thanks to an unlikely friendship that becomes fast family, his life doesn't boil down they same anymore. Not when he finally has a chance to leave a legacy"--Page 4 of cover.